2014
DOI: 10.4103/0301-4738.138621
|View full text |Cite
|
Sign up to set email alerts
|

Scleral depressed vitreous shaving, 360 laser, and perfluoropropane (C 3 F 8 ) for retinal detachment

Abstract: Purpose:To review the characteristics and outcomes of patients who underwent pars plana vitrectomy (PPV) with scleral depressed vitreous shaving, 360 degree peripheral endolaser, and 14% C3F8 gas for rhegmatogenous retinal detachment (RRD).Materials and Methods:A retrospective review of a consecutive series of patients who underwent primary repair of RRD by PPV with scleral depressed vitreous shaving, 360 degree peripheral endolaser, and 14% perfluoropropane (C3F8) was conducted. Patients with less than 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Kobashi et al [ 16 ] reported that although eyes with superior breaks exhibited slightly better results than eyes with inferior breaks, the primary anatomical success rate of the repair of RRD did not significantly differ between the eyes with inferior and superior breaks, which was in line with other previous studies [ 14 , 17 , 28 ]. On the other hand, Goto et al reported that the anatomical success rate of primary vitrectomy for RRD with inferior breaks was lower than that of RRD with superior breaks (80% versus 98%) [ 29 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Kobashi et al [ 16 ] reported that although eyes with superior breaks exhibited slightly better results than eyes with inferior breaks, the primary anatomical success rate of the repair of RRD did not significantly differ between the eyes with inferior and superior breaks, which was in line with other previous studies [ 14 , 17 , 28 ]. On the other hand, Goto et al reported that the anatomical success rate of primary vitrectomy for RRD with inferior breaks was lower than that of RRD with superior breaks (80% versus 98%) [ 29 ].…”
Section: Discussionsupporting
confidence: 84%
“…Over the last 40 years, there have been a variety of advancements in vitrectomy surgery including intraocular gases, increased vitreous cutter speeds, wide angle viewing systems, perfluorocarbon liquids, lighted and curved instruments, sutureless vitrectomy, and chandelier lights. These advancements have improved the surgeon's ability to perform a thorough evaluation of the peripheral retina due to the higher magnification and excellent illumination, which is crucial for detecting and treating all retinal breaks and relieving the vitreoretinal traction [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported after extensive vitreous removal [10,20,22]. A different study [29] utilized transillumination by light pipe to indent the eye in combination with TA to enhance visualization of the vitreous base for closer vitreous shaving; they reported less detachments after changing to the novel method.…”
Section: Plos Onementioning
confidence: 99%
“…Although controversial, use of small gauge instruments may reduce the incidence of postoperative cataract [ 71 , 72 ]. Peripheral vitrectomy with meticulous vitreous shaving is highly beneficial in eyes with RD, especially in complicated cases, in order to prevent redetachment or proliferative vitreoretinopathy (PVR) [ 73 75 ]. In eyes with cataract, combined phacoemulsification and pars plana vitrectomy is a good option, since it allows a better shaving of vitreous base.…”
Section: Introductionmentioning
confidence: 99%